1985
DOI: 10.1007/bf01837899
|View full text |Cite
|
Sign up to set email alerts
|

Event-related brain potential correlates of the processing of novel visual and auditory information in autism

Abstract: Event-related brain potentials (ERPs) elicited by visual and auditory stimuli were recorded from nonretarded individuals with autism (ages 13-25 years) and age-matched normal controls. In "no-task" conditions, subjects simply looked at or listened to these stimuli; only one difference was found between subject groups. Several ERP differences between groups were found in "task" conditions; subjects pressed a button at the occurrence of target stimuli intermixed with unexpected, novel stimuli and also with expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
80
0
3

Year Published

1987
1987
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(96 citation statements)
references
References 45 publications
12
80
0
3
Order By: Relevance
“…Further, neither the acoustic complexity nor the ''speechness'' quality of these stimuli affected the sensory discrimination of pitch in the autism group, as shown by their normal MMN amplitudes. This finding is in good agreement with the generally good behavioral performance on auditory target (acoustically simple and complex) detection tasks by adults and adolescents with autism (6,7,11) and with the normal behavioral pitch discrimination abilities in adults with autism (18).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Further, neither the acoustic complexity nor the ''speechness'' quality of these stimuli affected the sensory discrimination of pitch in the autism group, as shown by their normal MMN amplitudes. This finding is in good agreement with the generally good behavioral performance on auditory target (acoustically simple and complex) detection tasks by adults and adolescents with autism (6,7,11) and with the normal behavioral pitch discrimination abilities in adults with autism (18).…”
Section: Discussionsupporting
confidence: 86%
“…They include abnormalities in spontaneous looking (3), focused attention (5)(6)(7)(8)(9)(10)(11), and voluntary shifting of attention (12)(13)(14). Courchesne et al (12) proposed that the majority of the attentional deficits observed in autism might be caused by a cerebellar dysfunction that slows down the adaptation of the neural systems to the constantly changing neural processing demands.…”
mentioning
confidence: 99%
“…Specifically, autistic children may have a limited ability to process novel information (Courchesne et al, 1985). They have smaller and later P300s than healthy children.…”
Section: Autistic Disordermentioning
confidence: 99%
“…The P300 wave, in particular, has been studied in a variety of populations suffering from some obvious developmental disorder or thought to be at risk for developing some disorder. Populations studied include children with ADD (18); children with infantile autism (19); the offspring of schizophrenic parents (20); the children of alcoholic parents (21); and adults who were diagnosed as dyslexic, with or without concomitant attention deficit disorder, as children (Duncan, personal communication agnosed as not having ADD as children had normal voltages of the P300 wave; however, the late components of their ERPs (Fig. 4) appear to be asymmetrical.…”
Section: Attention-information Processingmentioning
confidence: 99%